2013
DOI: 10.1039/c3ra40734a
|View full text |Cite
|
Sign up to set email alerts
|

AIE (AIEE) and mechanofluorochromic performances of TPE-methoxylates: effects of single molecular conformations

Abstract: Two methoxy-substituted tetraphenylethylene (TPE) derivatives, tetra(4-methoxyphenyl)ethylene (TMOE) and tetra(3,4-dimethoxyphenyl)ethylene (TDMOE), were synthesized by McMurry reaction in high yields.The nearly centrosymmetric and natural propeller shape of TMOE and TDMOE excluded intermolecular effects, such as H or J-aggregation and p-p stacking, on their AIE (AIEE) and mechanofluorochromic performance. The crystal structures of TMOE and TDMOE, and theoretical calculations proved that their emission colours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 43 publications
(9 reference statements)
1
58
0
Order By: Relevance
“…[14,15] Mechano-responsive materials also usually exhibit emission properties under mechanical stress. [16][17][18] In most cases, this effect results from the formation of supramolecular nanostructures;m echanical stimulus triggers transitions between several crystalline and amorphous phases or between an aggregated and am onomeric state,w hich are responsible for changes in the luminescence emission. [19][20][21][22][23][24][25] Although mechano-responsive materials have been developed for mechanical stress sensing [20] and security tag applications, [21] owing to the limit of expression of both chirality and luminescence properties,m echano-responsive materials that enable control of CPL characteristics have been only two studies reported by Kawai [24] and Yamashita [25] groups.Inprevious studies,the researchers have reported the control of chirality in hydrogels composed of two components and al uminescence dissymmetry factor of two difluoroboron-b-diketonate complexes.I nc ontrast, the kinetically controlled mechano-responsive chiral supramolecular polymerization through the control of CPL property has not been reported, despite their benefits as the seed and building block in living supramolecular co-polymerizations.T herefore,t he investigation of CPL supramolecular polymerization generated by af inely tuned external stimulus (for example, rotation, pressure,a nd light) still remains as ignificant challenge.H erein, we report kinetic controlled CPL supramolecular polymerization with four l-o rd-a lanine branch side chains formed by the fine-tuning of am echanical stimulus.I nterestingly,C Da nd CPL signals were able to be finely tuned by controlling rotational speed;i ncreasing the rotational speed led to the acceleration of al arge enhancement of CD and CPL signals.…”
mentioning
confidence: 99%
“…[14,15] Mechano-responsive materials also usually exhibit emission properties under mechanical stress. [16][17][18] In most cases, this effect results from the formation of supramolecular nanostructures;m echanical stimulus triggers transitions between several crystalline and amorphous phases or between an aggregated and am onomeric state,w hich are responsible for changes in the luminescence emission. [19][20][21][22][23][24][25] Although mechano-responsive materials have been developed for mechanical stress sensing [20] and security tag applications, [21] owing to the limit of expression of both chirality and luminescence properties,m echano-responsive materials that enable control of CPL characteristics have been only two studies reported by Kawai [24] and Yamashita [25] groups.Inprevious studies,the researchers have reported the control of chirality in hydrogels composed of two components and al uminescence dissymmetry factor of two difluoroboron-b-diketonate complexes.I nc ontrast, the kinetically controlled mechano-responsive chiral supramolecular polymerization through the control of CPL property has not been reported, despite their benefits as the seed and building block in living supramolecular co-polymerizations.T herefore,t he investigation of CPL supramolecular polymerization generated by af inely tuned external stimulus (for example, rotation, pressure,a nd light) still remains as ignificant challenge.H erein, we report kinetic controlled CPL supramolecular polymerization with four l-o rd-a lanine branch side chains formed by the fine-tuning of am echanical stimulus.I nterestingly,C Da nd CPL signals were able to be finely tuned by controlling rotational speed;i ncreasing the rotational speed led to the acceleration of al arge enhancement of CD and CPL signals.…”
mentioning
confidence: 99%
“…On the contrary, the shift in the color of the polymorphs of 1 may be ascribed to different π-π stacking between adjacent calixarene dimer units, as 1 adopts the same conformation. [31][32][33][34][35] Combining AIE with control of packing arrangement to produce materials that exhibit stimuli-responsive switching between two or more solid phases with different emission characteristics still remains a challenge, [35][36][37][38][39] and would provide potential applications for smart materials. [40,41] The blue emitting crystals of 1 suffered thermal treatment for the sake of stimuli-responsive behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanochromic luminescence (MCL) refers to the phenomenon whereby an isothermal change in solid-state photoluminescence (PL) occurs where the material has two states, and at least one pathway is induced by mechanical stimuli like grinding, shearing, pressing, and stretching. [1] Plausible mechanisms for MCL indicate changes in the photophysical state of the chromophore, such as changes in the chemical structure, [2] aggregation, [3] intramolecular conformation, [4] and formation of intermolecular excimers. [5] MCL is expected to be applied to mechanical sensors, the detection of microenvironmental changes, [6] and optical memory.…”
Section: Introductionmentioning
confidence: 99%